2019
DOI: 10.3892/ijo.2019.4800
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Sirt6 promotes M2�macrophage transformation, alleviating renal injury in diabetic nephropathy

Abstract: In this study, we aimed to investigate the associations between Sirt6, macrophages and diabetic nephropathy (DN). Immunohistochemical, western blot and RT-qPCR analyses were performed to detect the expression levels of Sirt6, the markers of podocytes and monocytes and related inflammatory factors in the tissues of rats with streptozocin-induced DN. A series of cell experiments in isolated culture or the co-culture of macrophages and podocytes were conducted to examine the effects of the overexpression of Sirt6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 62 publications
1
48
0
Order By: Relevance
“…Colonic tissue is severely damaged by DSS treatment, and multiple types of cells participate in the histological and physiological changes, such as epithelial cells, macrophages, and neutrophils [ 33 ]. Interestingly, SIRT6 plays an important role in regulating these types of cells in the process of protecting the individual from damage or stress [ 34 , 35 ]. SIRT6 is globally overexpressed in TG mice used in this study, so we conjecture that SIRT6 functions in various cells to prevent against DSS-induced colitis in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Colonic tissue is severely damaged by DSS treatment, and multiple types of cells participate in the histological and physiological changes, such as epithelial cells, macrophages, and neutrophils [ 33 ]. Interestingly, SIRT6 plays an important role in regulating these types of cells in the process of protecting the individual from damage or stress [ 34 , 35 ]. SIRT6 is globally overexpressed in TG mice used in this study, so we conjecture that SIRT6 functions in various cells to prevent against DSS-induced colitis in mice.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has revealed that both increased M1 and decreased M2 play a crucial role in podocyte injury in vivo [ 37 ]. A series of cell experiments in isolated culture or the coculture of macrophages and podocytes was conducted to examine their interaction [ 20 , 38 , 39 ]. Our results showed that (HG) MS, the isolated culture of HG-treated macrophage, induced podocyte apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al suggested that the inhibition of M1 macrophage activation and the promotion of M2 macrophage transformation prevented podocyte injury [71]. Similarly, activation of M2 by Sirt6 protected podocytes against injury in a mimicked diabetic kidney microenvironment [72].…”
Section: Macrophage Phenotype and Diabetic Nephropathymentioning
confidence: 99%